2014
DOI: 10.1007/s40258-014-0106-9
|View full text |Cite
|
Sign up to set email alerts
|

Systematic Review of the Cost Effectiveness of Radiation Therapy for Prostate Cancer from 2003 to 2013

Abstract: Cost-effectiveness research of prostate radiation treatments allows patients, providers, and payers to better understand the true value of each treatment choice. Due to the variation in each of these analyses (e.g., costing, and disease and complication assumptions, etc.), it is difficult to generalize the results. One must be careful in drawing conclusions from these studies and extrapolating to individual patients, particularly with the clear utility dependence seen in the majority of these studies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
38
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 63 publications
(40 citation statements)
references
References 41 publications
1
38
0
1
Order By: Relevance
“…Prior studies have investigated the cost-effectiveness of various prostate cancer treatment modalities. Many of these studies have made comparisons among radiotherapy techniques, including brachytherapy and various radiotherapy techniques such as intensity-modulated radiotherapy (IMRT), stereotactic body radiotherapy (SBRT), and 3D-conformal radiotherapy (17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27). Other studies have focused on comparisons among surgical techniques (28)(29)(30).…”
Section: Discussionmentioning
confidence: 99%
“…Prior studies have investigated the cost-effectiveness of various prostate cancer treatment modalities. Many of these studies have made comparisons among radiotherapy techniques, including brachytherapy and various radiotherapy techniques such as intensity-modulated radiotherapy (IMRT), stereotactic body radiotherapy (SBRT), and 3D-conformal radiotherapy (17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27). Other studies have focused on comparisons among surgical techniques (28)(29)(30).…”
Section: Discussionmentioning
confidence: 99%
“…Another study by Amin et al 41 systematically reviewed the literature to identify articles that performed cost-effectiveness analysis of rt options for prostate cancer to identify the main cost drivers. Both studies also found large variations in the cost of rt between studies because of factors unrelated to the patient and the various treatment-related morbidities; however, neither study performed a thorough investigation of differences in costing components and sources in rt.…”
Section: Discussionmentioning
confidence: 99%
“…and gastrointestinal, among others, and has not been shown to be consistently cost effective (31)(32)(33). However, there are no previous studies examining the cost effectiveness of IMRT in the treatment of NSCLC.…”
Section: Original Researchmentioning
confidence: 99%